Oxidative Olefination of Benzylamine with an Active Methylene Compound Mediated by Hypervalent Iodine (III) - Rupanawar, Bapurao D.; Veetil, Sruthi M.; Suryavanshi, Gurunath (European Journal of Organic Chemistry, 2019)
Hypervalent iodine-mediated oxidative olefination of amines with an active methylene compound provides a rapid gateway towards the formation of electrophilic alkenes under mild reaction conditions in good to excellent yields. This is an efficient protocol for the preparation of substituted electrophilic alkenes.